1999
DOI: 10.1165/ajrcmb.20.5.3308
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c-erbB Receptors and Ligands in Human Bronchial Mucosa

Abstract: The epidermal growth factor receptor (EGFR, c-erbB1) plays a pivotal role in maintenance and repair of epithelial tissues; however, little is known about coexpression of c-erbB receptors and their ligands in human bronchial epithelium. We therefore analyzed the expression of these molecules in cultured bronchial epithelial cells and normal bronchial mucosa, using reverse transcription-polymerase chain reaction (RT- PCR), flow cytometry, and immunohistochemistry. Messenger RNA (mRNA) encoding EGFR, c-erbB2, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
97
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 50 publications
18
97
2
Order By: Relevance
“…We observed basal activation and phosphorylation of EGFR in the 16HBE cells, possibly due to autocrine release of EGFR ligands (e.g., EGF, TGF-␣, human bronchial EGF, which are expressed by 16HBE cells; Ref. 32). When the cells were transfected with siRNA Ecadherin for 3 days, a marked increase in basal EGFR phosphorylation occurred when compared with cells transfected with nontargeting siRNA (Fig.…”
Section: Increased Egfr Phosphorylation After E-cadherin Silencingmentioning
confidence: 80%
“…We observed basal activation and phosphorylation of EGFR in the 16HBE cells, possibly due to autocrine release of EGFR ligands (e.g., EGF, TGF-␣, human bronchial EGF, which are expressed by 16HBE cells; Ref. 32). When the cells were transfected with siRNA Ecadherin for 3 days, a marked increase in basal EGFR phosphorylation occurred when compared with cells transfected with nontargeting siRNA (Fig.…”
Section: Increased Egfr Phosphorylation After E-cadherin Silencingmentioning
confidence: 80%
“…ERBB3 was expressed in primary proliferating cultures of human bronchial epithelium. 364 In scrape-wounded adult lung epithelial monolayers, tyrosine phosphorylation of EGFR, ERBB2 and ERBB3 occurred immediately. 365 Smoking was associated with significant increases in EGFR and especially in ERBB3 in bronchial epithelial cells compared to nonsmokers.…”
Section: Respiratory Tissuesmentioning
confidence: 99%
“…For example, HB-EGF, amphiregulin and EGF have a widespread tissue distribution pattern, although TGF-a is expressed mainly in epithelial cells, macrophages and eosinophils. Immunolocalisation studies have revealed that EGF is primarily expressed in bronchial glands [218,219], although there is weak expression in the bronchial epithelium and smooth muscle [220]. Interestingly, stronger EGF immunoreactivity has been demonstrated in the bronchial epithelium, glands, smooth muscle [220] and submucosa [165] of asthmatic subjects compared with nonasthmatics.…”
Section: A Question Of Balancementioning
confidence: 99%
“…EPIDERMAL GROWTH FACTORS AND ASTHMA EGFR, ErbB2 and ErbB3 receptors are expressed in the epithelium of the upper and lower airways, as well as in primary cultures of human bronchial epithelial cells and human bronchial epithelial derived cell lines, such as H292 and 16HBE 14o- [217,219]. In asthma, it has been observed that the expression of EGFR is increased on the remaining epithelial cells around the site of damage, and on the apical side of the exposed basal cells [219].…”
Section: Functions Of Egfr Ligandsmentioning
confidence: 99%
See 1 more Smart Citation